Effects of finite temperature and pairing correlations in multi-A hypernuclei - Suleymanli, Bahruz; Bozkurt, Kutsal; Khan, Elias; Guven, Hasim; Margueron, Jerome (AMER PHYSICAL SOC, 2024)
The influence of finite temperatures and pairing correlations on the ground-state properties of multi-A A Ca, Sn, and Pb hypernuclei is explored using the finite-temperature Hartree-Fock-Bogoliubov approach and contact pairing interaction. A critical temperature is predicted and is in agreement with the Bardeen-CooperSchrieffer relationship kBTCA B T C A approximate to 0.5AT . 5 A T = 0 A , beyond which pairing correlations drop to zero. Particle densities, A single-particle energies, and nuclear radii are weakly impacted by pairing as well as by finite temperatures. However, other nuclear properties which are more sensitive to pairing correlations, such as A-pairing gaps, condensation energies, and abnormal densities are also more impacted by finite temperature, especially around the critical temperature. Furthermore, calculations show the occurrence of the pairing re-entrance effect in the 280 70 A Pb hyperon drip-line hypernucleus. Our study provides insight into the thermal evolution of A pairing, i.e., the emergence and vanishing of pairing correlations in multi-A A hypernuclei as a function of temperature.
Keywords: THERMAL EVOLUTION; NEUTRON-STARS; DENSITIES; COLLAPSE; Physics